Combining informal care and paid work: The use of work arrangements by working adult‐child caregivers in the Netherlands. (31st July 2017) - Oldenkamp, Marloes; Bültmann, Ute; Wittek, Rafael P.M.; Stolk, Ronald P.; Hagedoorn, Mariët; Smidt, Nynke
Abstract: An increasing number of people combine paid work with the provision of informal care for a loved one. This combination of work and care may cause difficulties, necessitating adaptations at work, i.e. work arrangements. The present study explores what types of work arrangements are used by working caregivers, and which caregiver, care and work characteristics are associated with the use of these work arrangements. Within the Lifelines Informal Care Add‐on Study (Lifelines ICAS), data on 965 Dutch informal caregivers in the North of the Netherlands were collected between May 2013 and July 2014 (response rate 48%), and data on 333 working adult‐child caregivers (aged 26–68 years, 82% female) were used in this study. A small majority (56%) of the working caregivers used one or more work arrangement(s): taking time off (41%), individual agreements with supervisor (30%), formal care leave arrangement (13%), and reduction in paid work hours (6%). Logistic regression analyses showed that long working hours (OR 1.06, 95% CI 1.01–1.08), and the experience of more health problems (OR 2.54, 95% CI 1.56–4.05) or a disrupted schedule due to caregiving (OR 2.50, 95% CI 1.66–3.78) increased the chance to have used one or more work arrangements. Lower educated working caregivers were less likely to have used a formal care leave arrangement (tertiary vs. primary education OR 2.75, 95% CI 1.13–6.67; tertiary vs. secondary education OR 1.27, 95% CI 1.27–5.09). Policy makers should inform working caregivers about the availability of the different work arrangements, with specific attention for low educated working caregivers. Employers need to consider a more caregiver‐friendly policy, as almost half of the working adult‐child caregivers did not use any work arrangement.